The Leamington Italian community : ethnicity and identity in Canada - Temelini, Walter, 1939- (Published for the Leamington Roma Club by McGill-Queen's University Press, 2019)
"The Leamington Italian Community intertwines personal and family stories with both empirical and intuitive writing to offer new historical insights into the complex social, economic, and psychological causes and effects of the migration phenomenon. Walter Temelini meticulously reconstructs the history of immigration and settlement in Leamington, Ontario, of Italians from the southern regions of Lazio, Molise, and Sicily. He explains how, despite their regional differences, three generations between 1925 and the 1990s forged a cohesive, socially conscious, and unique agricultural community by balancing their inherited values and their newly adopted Canadian economic opportunities. Temelini's groundbreaking research draws on testimonial and documentary evidence gathered from in-depth interviews with hundreds of residents, as well as on original archival information, and Italian-language histories translated by the author and previously unavailable to English-speaking readers. He concludes his study with an investigation into the award-winning novel Lives of the Saints by Nino Ricci, one of the community's most celebrated descendants. Drawing parallels between Ricci's narrative and the development of the community, Temelini demonstrates that ethnicity can be transformed successfully into a powerful universal archetype, and a creative force of identity. A pioneering and authoritative work, The Leamington Italian Community creates an intimate portrait within a global framework, delving into issues both timely and timeless, that will interest and inform the general and specialized reader alike."--